SCIENCE LEARNING IN PRIMARY SCHOOL IN THE PERSPECTIVE OF NATURE OF SCIENCE: A CASE STUDY IN THE FIFTH GRADE - Linda Hania Fasha (IKIP Siliwangi, 2020)
The case study of elementary school science learning is performed in the fifth grade of a primary school located in Bandung. The study aims to describe the extent to which the nature of the sains principle is identified through classroom learning. In this study, the data used include the document of learning draft, teacher’s point of view towards science and its learning, learning activities documentation, and school principal’s point of view about learning in general including the expectation towards science learning. In terms of the main objective of science learning, students’ initial ideas about science triggered in the context of learning problems used can be explored properly through answers to questions raised by the teacher as well as students’ conclusions or statements on the studied problem. The study has successfully identified seven aspects of the nature of science in learning, although the depth and wholeness of these aspects still need further development in the future. Based on the result of the study, it is concluded that a progressive effort is still needed to improve teachers’ beliefs system and their learning.